Pengembangan Media Pembelajaran Melalui Software Lectora Inspire Materi Wujud Zat Dan Perubahannya Berbasis Model Pembelajaran Problem Based Learning - Desih, Desih; Taufik, M; Setiawan, Sigit (Universitas Muhammadiyah Magelang, 2023)
The use of technology-based learning media is able to raise students' learning motivation, especially in science and science learning. The aim of this research is to find out the development process, feasibility and response of students to the Lectora Inspire media, material on the form of substances and its changes based on the problem based learning model in class IV of Sindangmandi State Elementary School. The research and development (R&D) method used is the ADDIE model which consists of five stages, namely Analyze, Design, Development, Implementation and Evaluation. The research was conducted on 22 students in class IV of Sindangmandi State Elementary School. Based on the research results, Lectora Inspire media is very suitable for use in learning activities. This is proven by the validation results carried out by experts. Validation from two media experts with a percentage of 89.5% is in the